2014
DOI: 10.1515/secm-2014-0092
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of pozzolanic activity of volcanic rocks from the northeast of the Black Sea

Abstract: Mineralogical and chemical properties, as well as the pozzolanic activities, of the volcanic rocks in the northeast of the Black Sea were examined. Physical and mechanical tests were conducted on samples collected from the study area and the feasibility of using volcanic rocks as pozzolanic admixture in the concrete industry was investigated. Mortar samples containing admixture in the ratios of 0%, 10%, 20%, 30%, 40%, and 50% were prepared by keeping fineness of pozzolanic admixtures fixed. By using these mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Hence, the use of supplementary cementitious materials commonly reached by SiO 2 , Al 2 O 3 , and Fe 2 O 3 are mostly recommended to be added in concrete for minimizing cement content, to achieve good concrete properties, cost reduction, and reduce environmental pollution coming due to ordinary Portland cement production [3]. Supplementary cementitious materials in concrete mixtures contribute a lot of significance to the fresh and hardened properties of concrete like enhancing workability, reducing the heat of hydration, lowering permeability, improving ultimate strength, and durability [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Hence, construction industries are potentially using one or another supplementary cementitious material commonly identified as pozzolana [8,20].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the use of supplementary cementitious materials commonly reached by SiO 2 , Al 2 O 3 , and Fe 2 O 3 are mostly recommended to be added in concrete for minimizing cement content, to achieve good concrete properties, cost reduction, and reduce environmental pollution coming due to ordinary Portland cement production [3]. Supplementary cementitious materials in concrete mixtures contribute a lot of significance to the fresh and hardened properties of concrete like enhancing workability, reducing the heat of hydration, lowering permeability, improving ultimate strength, and durability [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Hence, construction industries are potentially using one or another supplementary cementitious material commonly identified as pozzolana [8,20].…”
Section: Introductionmentioning
confidence: 99%
“…So, a balanced approach that finds the optimum uses of these materials is required. The study carried out by Cullu et al [14] showed that an amount of trass up to 20% cement replacement is effective in increasing in mechanical performance of mortar samples. An increase in strength at 7 days, 28 days, and 90 days by around 5-20% is observed with the incorporation of 18% of trass as a cement replacement [15].…”
Section: Introductionmentioning
confidence: 99%
“…Costafreda et al [ 11 ] recommend the industrial manufacturing of pozzolanic cement with the proportions 75:25% and 70:30% with natural pozzolans since they provide practically the same mechanical strength. Çullu et al [ 42 ] observed that increasing the percentage of various natural pozzolans at the expense of cement produced a decrease in compressive strength, proposing that the optimum dose may be 10%. Turanli et al [ 43 ] found that the compressive strength of mortar containing large amounts of volcanic ash was lower than that of Portland cement at any age less than 90 days.…”
Section: Introductionmentioning
confidence: 99%